Lifelong learning in restaurant business - Rakicevik, Gabriela (Array, 2008)
Lifelong learning is the reality in all successful service industries. In the field of the hotel and tourism industry, it is very important to implement this concept. That will assure to achieve high level of quality - to be competitive on the market, and as feedback to get a big number of satisfied guests. There are different issues to discuss for the concept of lifelong learning. One of the most important thing is the need and interest for permanent education from both sides: employee and employer. The other issue is: according to law who is competent to organize and offer different forms of lifelong learning; who will recognize the certificate and/or diploma!? Financial aspect has big influence as well: who will cover the expences for any kind of education for already employed people. Methods and techniques for lifelong learning varry according to target group, topic, time, department in the hospitality property etc. Training is very popular method for permanent education. In general there are two basic types of training: the one-on-one training method and group training. Much of the training in restaurant business is done individually. Most one-on-one training is conducted by implementation of the following techniques: buddy system, cross-training,computer training and video. There are many different techniques that can be used in group training: classroom, lecture, demonstration, role-playing, games, professional trainers. In some countries, very popular is the concept of service learning